Protection of Consumer Rights in Online Transactions (E-Commerce) at Suru-Suru All Delivery Panyabungan According to Sharia Business Ethics - Afridah, Afridah; Nasution, Darwin (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
The rapid advancement of information technology has significantly impacted the communication process, making it crucial in today's fast-paced world. Internet technology has been instrumental in meeting this need, but there is no consensus on the definition of E-Commerce, as it is a complex issue involving science, technology, economics, and law. A descriptive analysis was used to analyze the importance of legal protection for online business users, focusing on business ethics in the context of buying and selling developments. The results of this study show that Suru-Suru All Delivery has fulfilled consumer rights as stipulated in Law Number 8 of 1999 on Consumer Protection, as seen from the interviews conducted by the researcher with consumers and the director of Suru-Suru All Delivery. Consumer protection in online transactions (E-Commerce) at Suru-Suru All Delivery is fundamentally in accordance with Sharia business ethics because the consumer protection provided by Suru-Suru All Delivery aligns with the principles of Sharia business ethics.